Determinan Kualitas Laporan Keuangan - Wiwik Pratiwi; Utami Diyah Lestary (Universitas Muhammadiyah Jakarta, 2020)
This research is in the context of understanding the extent to which human resource competencies, the use of information technology and the application of the accrual basis method affect the quality of financial statements. The population of this research is companies in the Central Jakarta and East Jakarta areas using primary data. The sampling technique in this research uses the stratified random sampling method in which the population has heterogeneous members with disproportionate strata. Multiple linear regression analysis as a data analysis technique. The results of this research indicate that the competence of human resources, the use of information technology and the application of the accrual basis method either partially or simultaneously have a positive and significant effect on the quality of financial statements